Barbaram, a bicyclic neolactam from the root and stem of Lycium barbarum. Issue 1 (2nd January 2021) - Lan, Ting; Xu, Wei; Xu, Tian-Qi; Xia, Zhao; Zhang, Hai-Xin; Zhan, Ya-Ping; Zhou, Guang-Xiong
Abstract: Barbaram (1 ), a neolactam together with other five known compunds (2 –6 ) was isolated from the EtOAc-soluble fraction of an EtOH extract of the root and stem of Lycium barbarum by using silica gel, Sephadex LH-20 column chromatography and semi-preparative RP-C18 HPLC. Based on HR-TOF-MS, NMR spectral data, quantum chemistry ECD calculations and referencing to the data reported earlier, the structures of these compounds (1 –6 ) were determined, specially including the absolute configuration of the neolactam (1 ). Compounds 2 and 4 showed significant anti-inflammatory activity in LPS-induced RAW 264.7 macrophages with the IC50 values of 8.98 ± 0.57 μM, 6.68 ± 0.77 μM. Abstract :